Force‐frequency relationship and early relaxation kinetics are preserved upon sarcoplasmic blockade in human myocardium. Issue 20 (22nd October 2018) - Chung, Jae‐Hoon; Canan, Benjamin D.; Whitson, Bryan A.; Kilic, Ahmet; Janssen, Paul M. L.
Abstract: In this study, we investigated the quantitative and qualitative role of the sarcoplasmic reticulum (SR) in the regulation of the force‐frequency relationship (FFR). We blocked the function of SR with cyclopiazonic acid (CPA) and ryanodine and measured twitch kinetics and developed force at various stimulation frequencies in nonfailing and failing intact human right ventricular trabeculae. We found that developed forces are only slightly reduced upon SR blockade, while the positive FFR in nonfailing trabeculae and negative FFR in failing trabeculae were both preserved. The contraction kinetics (dF/dt, dF/dt/F, and time to peak), however, were significantly slower at all frequencies tested. Kinetics of first 50% of relaxation (RT50) was not affected by SR blockade. Kinetics of entire relaxation process (RT90) was overall slower at low frequencies, but not at high frequencies. From our findings, we conclude that the SR is not essential for FFR, and its role in regulation of FFR lies mostly in contraction kinetics. Unlike small rodents, human myocardium contractile function is near‐normal in absence of a functional SR with little changes in contractile force, and with preservation with the main regulation of FFR. Abstract : We investigated the quantitative and qualitative role of the sarcoplasmic reticulum (SR) in the regulation of the force‐frequency relationship (FFR). In non‐failing and failing human cardiac ventricular tissue, the SR is not essential for FFR, and its role in regulation of FFR lies mostly in contraction kinetics.